Optimization of medium composition for actinorhodin production by Streptomyces coelicolor A3(2) with response surface methodology - Elibol, M (Elsevier Sci Ltd, 2004)
Optimization of the fermentation medium for maximization of actinorhodin production by Streptomyces coelicolor A3(2) was carried out. Response surface methodology (RSM) was applied to optimize the medium constituents. A 2(4) full-factorial central composite design (CCD) was chosen to explain the combined effects of the four medium constituents, viz. sucrose, glucose, yeast extract (YE) and peptone, and to design a minimum number of experiments. The P-values of the coefficients for linear, quadratic and cross-product effect of sucrose and glucose concentration were <0.0001, suggesting that these were critical variables having the greatest effect on the production of actinorhodin in the complex medium. The optimized medium consisting of 339 g/l sucrose, 1 g/l glucose, 1.95 g/l YE and 2.72 g/l peptone predicted 195 mg/l of actinorhodin which was 32% higher than that of the unoptimized medium. The amounts of glucose, YE and peptone required were also reduced with RSM. (C) 2003 Elsevier Ltd. All rights reserved.
Keywords: antibiotic; Streptomyces coelicolor; response surface methodology; optimization